An Analysis of Blooket Performance in Intermediate Mandarin Reading Course - Tiffany Qorie; Yogi Bagus Adhimas; Audrey Gabriella Titaley; Huiling Ren (Mandarinable: Journal of Chinese Studies, 2025)
This study aims to analyze the effectiveness of using a Blooket as a gamified learning tool in an intermediate-level Mandarin reading class. Using a descriptive quantitative approach based on User Experience (UX), additional data were collected through questionnaires, interviews, and non-participatory observations. The findings reveal that the highest scores were seen in the stimulation and efficiency aspects, indicating that Blooket improves student motivation and facilitates a faster learning process. Conversely, the reliability aspect obtained the lowest score, primarily due to network instability and students’ inaccuracy in reading Chinese characters. Overall, Blooket demonstrates great potential as a foreign language learning tool. However, its implementation should be supported by a comprehensive pedagogical strategy to optimize the benefits of gamification and further develop learners’ language proficiency.